Easiness of Use and Validity Testing of VS-SENSE Device for Detection of Abnormal Vaginal Flora and Bacterial Vaginosis. (18th July 2010) - Donders, Gilbert G. G.; Marconi, Camila; Bellen, Gert
Abstract : Accessing vaginal pH is fundamental during gynaecological visit for the detection of abnormal vaginal flora (AVF), but use of pH strips may be time-consuming and difficult to interpret. The aim of this study was to evaluate the VS-SENSE test (Common Sense Ltd, Caesarea, Israel) as a tool for the diagnosis of AVF and its correlation with abnormal pH and bacterial vaginosis (BV). The study population consisted of 45 women with vaginal pH≥ 4.5 and 45 women with normal pH. Vaginal samples were evaluated by VS-SENSE test, microscopy and microbiologic cultures. Comparing with pH strips results, VS-SENSE test specificity was 97.8% and sensitivity of 91%. All severe cases of BV and aerobic vaginitis (AV) were detected by the test. Only one case with normal pH had an unclear result. Concluding, VS-SENSE test is easy to perform, and it correlates with increased pH, AVF, and the severe cases of BV and AV.